Erythrodermic flare‐up of psoriasis with COVID‐19 infection: A report of two cases and a comprehensive review of literature focusing on the mutual effect of psoriasis and COVID‐19 on each other along with the special challenges of the pandemic - Elham Behrangi; Afsaneh Sadeghzadeh‐Bazargan; Nastaran Salimi; Zoha Shaka; Mohammad Hosein Feyz Kazemi; Azadeh Goodarzi (Clinical Case Reports, 2022)
Abstract The COVID‐19 pandemic has been extra challenging for patients with chronic diseases. Psoriasis is one of the chronic conditions that its treatment mostly relies on immunosuppressants. In this study, we report two cases with a long history of psoriasis that COVID‐19 infection caused them to undergo erythrodermic psoriasis.